Gambaran Tingkat Pengetahuan Masyarakat tentang Swamedikasi Obat Apotek di Kabupaten Sleman dan Yogyakarta - Marlian, Ririn Irma; Shalahuddin Al Madury; Sual, Kezia Charania Vinly Marcya; Joangga, Ilham; Alvita, Stefani Nuri; Rahmawati, Nisa; Azizah, Mifza; Amalia, Siska (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2025)
Background: Self-medication is the use of drugs by individuals to treat perceived or self-diagnosed health conditions without consulting healthcare professionals. While self-medication can offer benefits such as faster relief of symptoms without the need to visit healthcare facilities, improper practices in obtaining, using, storing, and disposing of medications remain common in the community. Objective: This study aims to describe the public’s level of knowledge regarding self-medication. The findings help to strengthen health behavior theories that emphasize the role of knowledge as a key determinant in responsible self-medication practices. Methods: A descriptive research design was employed using an observational method through a questionnaire consisting of 20 statements. A total of 90 respondents participated in the study with randomized sampling. Results: The majority of respondents were aged 18–25 years (28.88%), female (64.44%), worked as housewives (25.55%), and had completed senior high school (63.33%). The level of knowledge about self-medication was mostly in the